Caracterización microbiológica y nutricional del suero lácteo de las industrias queseras del cantón Latacunga. - Palomo Pilliza, Jonathan Efraín (2023)
The present study is to know the whey that is a by-product that is obtained through the coagulation of milk in the elaboration of cheeses. Latacunga is one of the cantons of Cotopaxi that discards the whey the most due to ignorance of the usable nutritional value that can be given to it, for which the importance of characterizing it has been determined through a process that allows us to collect information, since in the The vast majority of cheese companies do not take advantage of this by-product, causing waste and the opportunity to benefit through the development of new innovative products. For this, a research methodology was used through different techniques in the first instance with the collection of serum samples from 32 Latacungo cheese companies to later analyze them in laboratories of the Technical University of Cotopaxi and the external SETLAB laboratory in the city of Riobamba. The analyzes were carried out with test methods of the NTE INEN 2594-2011 standard in force in Ecuador. For the microbiological analyzes, a count of mesophilic aerobics is recorded with results of 1, 950,000 in the most significant number of the 32 samples that consequently do not present a good sanitary quality, exceeding the maximum limit of 100,000 dictated by the regulations, regarding the recount of Eschericha coli presents absence in the same way with salmonella that reflects absence, therefore it is complying with the established regulations. On the other hand, the nutritional analyzes carried out with the S - S_lactoscan equipment allowed to reveal the percentage in lactose with ranges from 2.46% to 4.96% and protein that fluctuates between 2.10% to 3.60% taking into account note that they are within the parameters allowed in the serum regulation regulations. In the same way, with the microbiological and nutritional results, a comparison was established with the INEN standard to obtain knowledge of whether it complies with the permissible limits to consider the use of whey in the food industry in the future.